TINJAUAN YURIDIS PENERAPAN PLEA BARGAINING UNTUK MENINGKATKAN EFISIENSI PERADILAN DI INDONESIA - Tristanto, Yunizar Wahyu (IAIN Tulungagung, 2018)
The case handling system implemented in Indonesia currently spends much time and effort. Indonesian criminal justice often experiences cases of accumulation or over capacity, criminal cases that cannot be resolved by judges in Indonesia every year continues to increase. To improve the quality of the handling of cases, there must be a change in the criminal justice system. An effective and efficient criminal justice system is necessary, due to many unresolved cases in the court. Indonesia is already in the process of making changes to the Criminal Procedure Code (KUHAP), in the Criminal Procedure Code there is a Special Line system to facilitate the examination in the hearing. The system adopted the western system known as Plea Bargaining. Plea Bargainings objective is the same as the Special Line for the efficiency of case handling time. The application of the Plea Bargaining concept is considered as a way out to overcome the accumulation of cases in the Indonesian judiciary, so that the principles of justice that are fast, simple and low-cost can be realized.Keywords: Criminal Case, Effective, Efficient, Special Line, Plea Bargaining